Cancer of the vulva: genetic aspects of pathogenesis - V V Sobolev; Z A Nevozinskaya; A G Soboleva; I M Korsunskaya (IP Berlin A.V., 2018)
The review is devoted to genetic research in cancer of the vulva. In genetic changes, the mutation irreversibly changes the nucleotide sequence of DNA, or the number of copies of chromosomes changes per cell. In epigenetics, the nucleotide sequence remains unchanged, but gene activity is regulated by methylation of DNA or modification of histones. Most of the studies analyzed are devoted to the study of mutations in the TP53 gene. Many studies indicate that somatic mutations are more common in HPV-negative than in HPV-positive patients. Epigenetic studies in the main devoted to hypermethylation. The gene CDKN2A is most often studied in epigenetic terms. For most of the studied genes, hypermethylation occurs more often in squamous cell carcinoma of the vulva than in the precursors.